Immobilization of laccase on modified silica: Stabilization, thermal inactivation and kinetic behaviour in 1-ethyl-3-methylimidazolium ethylsulfate ionic liquid - Ana P. M. Tavares (2013)
Laccase was immobilized on modified silica carrier. The immobilization conditions, pH and enzyme concentration were optimized. Operational stability of 10 reaction cycles showed that immobilized laccase in buffer was stable, presenting an activity loss <30%. Nevertheless, a high decrease >80% was obtained in ionic liquid (IL) solution. Activity of immobilized laccase was maintained when incubated in IL After 7 days of incubation, immobilized laccase lost 30-50% of its initial activity. Immobilization also improved thermal stability of laccase in the presence of IL. Enzyme kinetics was modelled with Michaelis-Menten model. The K-m value for free laccase increases significantly with the IL concentration. Slight differences were found in V-m, for free enzyme. Unusual kinetic behaviour was obtained for immobilized laccase in IL: Both V-m and K-m increased with IL concentration, resulting in increased catalytic efficiency of the immobilized enzyme in presence of IL. (C) 2013 Published by Elsevier Ltd.